2008
DOI: 10.1103/physrevlett.101.108303
|View full text |Cite
|
Sign up to set email alerts
|

Conformation and Dynamics of DNA Confined in Slitlike Nanofluidic Channels

Abstract: Using laser fluorescence microscopy, we study the shape and dynamics of individual DNA molecules in slitlike nanochannels confined to a fraction of their bulk radius of gyration. With a confinement size spanning 2 orders of magnitude, we observe a transition from the de Gennes regime to the Odijk regime in the scaling of both the radius of gyration and the relaxation time. The radius of gyration and the relaxation time follow the predicted scaling in the de Gennes regime, while, unexpectedly, the relaxation ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

23
219
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 132 publications
(247 citation statements)
references
References 26 publications
23
219
5
Order By: Relevance
“…DNA has played a key role in the experimental tests of theories of a polymer confined to a slit [1][2][3][4][5][6][7][8][9][10][11][12][13][14] or a channel [15][16][17][18][19][20][21][22][23][24][25][26][27], in particular the models by de Gennes and coworkers for weak confinement [28,29] and Odijk for strong confinement [30,31]. The key results of this body of work have been summarized in several recent reviews [32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…DNA has played a key role in the experimental tests of theories of a polymer confined to a slit [1][2][3][4][5][6][7][8][9][10][11][12][13][14] or a channel [15][16][17][18][19][20][21][22][23][24][25][26][27], in particular the models by de Gennes and coworkers for weak confinement [28,29] and Odijk for strong confinement [30,31]. The key results of this body of work have been summarized in several recent reviews [32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the width of presently-available confining nano-devices (a channel, a slit, a pit etc.) can be set to compete with one or more of the characteristic lengths of a DNA molecule and hence allow for probing different physical regimes [8,[11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge there exist only * Electronic address: michelet@sissa.it † Electronic address: orlandini@pd.infn.it a limited number of experimental and numerical studied of the size and shape of DNA molecules in nanoslits [8,18,[31][32][33]. These seminal studies have addressed the interesting issue of whether multiple scaling regimes exist in linear DNA filaments inside slits.…”
Section: Introductionmentioning
confidence: 99%
“…A number of single molecule fluorescence microscopy studies have recently investigated the structure and dynamics of confined DNA trapped between parallel * Electronic address: chaudhuri@amolf.nl † Electronic address: mulder@amolf.nl plates [8][9][10][11] or within cylindrical geometries [12][13][14] with the confining dimensions typically of the order of, or smaller than, the bulk radius of gyration of the polymer.…”
Section: Introductionmentioning
confidence: 99%
“…In particular Bonthuis et al [10] have recently observed DNA confined to parallel-plate nanochannels, showing among others an interesting non-monotonic variation of the two-dimensional (2d) projected radius of gyration with the distance between channel walls.…”
Section: Introductionmentioning
confidence: 99%